Addressing the gender pain gap - Dawes, JM; Bennett, DL (Cell Press, 2021)
Chronic pain is more common in women, however, our understanding of sex-specific differences in pain mechanisms is rudimentary. In this issue of Neuron, Luo et al., (2021) delineate a novel sex-specific neuro-immune pathway contributing to enhanced mechanical pain in females.